Thin‐film CdTe detector for microdosimetric study of radiation dose enhancement at gold‐tissue interface. (8th September 2016) - Paudel, Nava Raj; Shvydka, Diana; Parsai, E. Ishmael
Abstract : Presence of interfaces between high and low atomic number (Z) materials, often encountered in diagnostic imaging and radiation therapy, leads to radiation dose perturbation. It is characterized by a very narrow region of sharp dose enhancement at the interface. A rapid falloff of dose enhancement over a very short distance from the interface makes the experimental dosimetry nontrivial. We use an in‐house‐built inexpensive thin‐film Cadmium Telluride (CdTe) photodetector to study this effect at the gold‐tissue interface and verify our experimental results with Monte Carlo (MC) modeling. Three‐micron thick thin‐film CdTe photodetectors were fabricated in our lab. One‐, ten‐ or one hundred‐micron thick gold foils placed in a tissue‐equivalent‐phantom were irradiated with a clinical Ir‐192 high‐dose‐rate (HDR) source and current measured with a CdTe detector in each case was compared with the current measured for all uniform tissue‐equivalent phantom. Percentage signal enhancement (PSE) due to each gold foil was then compared against MC modeled percentage dose enhancement (PDE), obtained from the geometry mimicking the experimental setup. The experimental PSEs due to 1, 10, and 100 μ m thick gold foils at the closest measured distance of 12.5 μ m from the interface were 42.6 ± 10.8, 137.0 ± 11.9, and 203.0 ± 15.4, respectively. The corresponding MC modeled PDEs were 38.1 ± 1., 164 ± 1, and 249 ± 1, respectively. The experimental and MC modeled values showed a closer agreement at the larger distances from the interface. The dose enhancement in the vicinity of gold‐tissue interface was successfully measured using an in‐house‐built, high‐resolution CdTe‐based photodetector and validated with MC simulations. A close agreement between experimental and the MC modeled results shows that CdTe detector can be utilized for mapping interface dose distribution encountered in the application of ionizing radiation. PACS number(s): 29.40.Wk, 73.50.Pz, 87.53.Jw, 87.55.K‐